The Impact of Using Interactive Whiteboards in Learning Fiqh at Elementary School - Herza, Naufal; Amra, Abhanda; Pebrina, Rizki; Mudinillah, Adam (Yayasan Adra Karima Hubbi, 2024)
Fiqh is one of the important subjects in elementary school that aims to equip students with knowledge and practical skills about worship and daily life in accordance with Islamic law. Effective and interesting fiqh learning is very important to foster students' love for religion and encourage them to practice Islamic teachings in their daily lives. The learning media used in fiqh learning is often less interesting and interactive, making students easily bored and not excited. To find out the extent of students' understanding of the material in the use of interactive and fun whiteboards and to find out how the influence of Interactive whiteboards in increasing a child's learning motivation using quantitative methods to find out the extent of students' understanding of the material in the use of interactive and fun whiteboards and to find out how the influence of Interactive whiteboards in increasing a child's learning motivation. And allows students to interact directly with learning materials, so they are more active and involved in the learning process. the results of this study indicate that the use of interactive whiteboards in fiqh learning can increase the learning interest of elementary school students. The results showed that students taught with interactive whiteboards were more interested in learning fiqh compared to students taught with traditional methods can help students understand the material more easily and enjoyably through interactive presentation of material, such as images, videos, animations, and simulations. Therefore, the use of interactive whiteboards can be one of the alternatives to improve student learning achievement in learning fiqh in elementary schools. However, it is important to note that teaching tools in the form of interactive whiteboards must be used accurately and creatively to achieve optimal results.